Model Pembelajaran Group Investigation terhadap Kemampuan Pemecahan Masalah Siswa Pada Materi Pola Hidup Gotong Royong Kelas IV - Sukma, Peggy Melati; Fanny, Arif Mahya (Universitas Muhammadiyah Magelang, 2025)
This study was motivated by the low ability of fourth-grade students to diagnose problems and formulate alternative strategies, as well as the dominance of lecture-based teaching methods and rote memorization in the classroom. The lack of challenging problems in daily learning has hindered the development of students’ critical thinking skills. This research aims to examine the effect of the Group Investigation learning model on students’ problem-solving abilities in the topic of cooperative living. The study employed a One-Group Pre-test-Post-test design with a quantitative approach. The sample consisted of 25 fourth-grade students from SD Rahmat Surabaya. Data were collected through problem-solving tests (pre-test and post-test), observation, and documentation as supporting instruments. Data were analyzed using the paired sample t-test. The results showed an increase in the average score from 53.4 (pre-test) to 77.6 (post-test), with a significance value of 0.000 (p < 0.05). This indicates a positive and significant effect of the Group Investigation model on students’ problem-solving abilities. Additionally, the effect size value of 2.49 falls into the very high category, suggesting that the model is highly effective in enhancing problem-solving skills. Therefore, the Group Investigation model is recommended for promoting active and collaborative student engagement in the learning process.